MultiMeta: an R package for meta-analyzing multi-phenotype genome-wide association studies. - Vuckovic, D; Gasparini, P; Soranzo, N; Iotchkova, V (Bioinformatics, 2015)
UNLABELLED: As new methods for multivariate analysis of genome wide association studies become available, it is important to be able to combine results from different cohorts in a meta-analysis. The R package MultiMeta provides an implementation of the inverse-variance-based method for meta-analysis, generalized to an n-dimensional setting. AVAILABILITY AND IMPLEMENTATION: The R package MultiMeta can be downloaded from CRAN. CONTACT: dragana.vuckovic@burlo.trieste.it; vi1@sanger.ac.uk SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.